Language acquisition as complex category formation - Lotto, A J (Phonetica, 2000)
Purported units of speech, e.g. phonemes or features, are essentially categories. The assignment of phonemic (or phonetic) identity is a process of categorization: potentially discriminable speech sounds are treated in an equivalent manner. Unfortunately the extensive literature on human categorization has typically focused on simple visual categories that are defined by the presence or absence of discrete features. Speech categories are much more complex. They are often defined by continuous values across a variety of imperfectly valid features. In this paper, several kinds of categories are distinguished and studies using human subjects, animal subjects and computational models are presented that endeavor to describe the structure and development of the sort of complex categories underlying speech perception.